Arquitetura como interface para a informação: sobre a espacialização das tecnologias da informação rumo a práticas colaborativas - Isabela Lages de Andrade (2010)
This study examines an intersection between the spatialization of information and CSCW - Computer Supported Collaborative Work. More specifically it is argued the possibility of influence of the spatial distribution of ICT (information and communication technologies) on the interactions between members of two remotely connected laboratories. Spatialization (concerning the provision in space of sound, visual, tactile elements in order to achieve aesthetic or perception effects ) is addressed through the concept of physical computing and under the specificity of ambient displays. It starts with the assumption thatspatialization can contribute to issues related to social presence in remote connections, or telepresence, conveying environmental information that normally go unnoticed through chat tools or videoconferencing, which do not exploit the testimonial nature of spaces.Essentially, the work seeks alternatives to the GUI, Graphical User Interface, which allowed a major technological breakthrough and allowed to implement a series of tasks, but nevertheless still presents many limitations. The lack of support for informal communications is one of those limitations, as well as the little engagement of body movements allowed and their attendant discomforts, in addition to users excessive concentration of attention in some inappropriate situations or excessive and unnecessary details to some contexts. Issues related to proxemics are also discussed in order to analyze the possibility of communication between attendance environments geographically distant and remotely connected. Through a series of experimental studies between LAGEAR (Graphic Laboratory for Architectural Experimentation) School of Architecture at UFMG (Federal University of Minas Gerais) and LCG (Laboratory of Computer Graphics) of FAU / UFU (Faculty of Architecture and Urban Planning at Federal University of Uberlandia), some situations are tested. A spatialized interface is developed in order to observe how the spatialization of information models the interaction between people and which would be the implications of connecting two ambiences, beyond sharing data on the computer screen. Therefore, information such as the number of people in a room, as well as the noise levelin the same room are captured by sensors and sent via Internet to another laboratory, 550 km apart. Subsequently, they are displayed in a spatially distributed way. In the conclusions, it was observed that in situations where collaboration was not formalized, such as for someone who suddenly enters a room, the interface was very effective. In situations of formal work, though, the interface was very poorly effective, because it was overshadowed by more objective tools such as a camera or a chat environment. For the context of collaborative work discussed here, spatialized interfaces worked best in complementarity with traditional GUI tools and not in substitution. What must be searched for is a rescue of an already lost balance: nowadays, tangible predispositions are insufficient while the center of attention is overloaded.